2015
DOI: 10.5501/wjv.v4.i2.36
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions between hepatitis B virus and delta virus

Abstract: HBV HBsAgs. While HBsAg is the only protein required by HDV, the exact interaction sites between the S protein and pre-mature HDV are not well defined yet. In fact, these sites are distributed along the S protein with some hot spots for the envelopment process. Moreover, in most clinically studied samples, HDV infection is associated with a dramatically reduced HBV viral load, temporarily or permanently, while HBsAg resources are available for HDV packaging. Thus, beyond interacting with HBV envelope proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
(54 reference statements)
1
20
1
Order By: Relevance
“…Hepatitis delta virus (HDV) co-infection or superinfection in hepatitis B virus (HBV)-infected individuals is the most severe form of chronic hepatitis. Although HBV DNA is often suppressed in co-infected patients, fluctuating or persistently high levels of HBV viraemia occur in delta hepatitis [1,2]. We recently reported the distinct mutational pattern in the HDV genome from a nationwide Iranian cohort, where the prevalence of HDV is high [3].…”
mentioning
confidence: 96%
“…Hepatitis delta virus (HDV) co-infection or superinfection in hepatitis B virus (HBV)-infected individuals is the most severe form of chronic hepatitis. Although HBV DNA is often suppressed in co-infected patients, fluctuating or persistently high levels of HBV viraemia occur in delta hepatitis [1,2]. We recently reported the distinct mutational pattern in the HDV genome from a nationwide Iranian cohort, where the prevalence of HDV is high [3].…”
mentioning
confidence: 96%
“…As the precise impact of IFN-therapy on HDV replication is unknown, it is also possible that HDV might interfere with IFN-therapy which is acting as an eliminator of its helper virus (Shirvani- Dastgerdi and Tacke, 2015). For IFN-therapy that does not achieve this very high efficacy, we found that HBV viremia settles to a level of HBV viremia that does not represent full elimination (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The need for such high efficacy inhibition could be attributed to the omission from our model of other mechanisms such as cytolytic killing of infected cells and the loss of intracellular quantities during cell proliferation that contribute to HBV clearance (Murray and Goyal, 2015). HDV infection dramatically reduces HBV viral load while maintaining HBsAg levels (Shirvani- Dastgerdi and Tacke, 2015). Thus elimination of HDV infection might first require substantial reduction in levels of cccDNA, the HBV template, which can only be achieved by IFNtherapy with very high efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small HDV circular genome is only ca 1.7 kb in length and is stabilized by extensive intramolecular base pairing. HDV encodes a single ORF that encodes the delta antigen (HDAg), which exists as two isoforms, the small and large HDAg [22]. HDV is considered a subviral satellite as it requires the HBV envelope proteins to form infectious virions.…”
Section: Hepatitis C B and Delta Virusesmentioning
confidence: 99%